2020
DOI: 10.1109/access.2020.2984794
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variations of Terrestrial Water Storage in Upper Indus Basin Using GRACE and Altimetry Data

Abstract: Gravity Recovery and Climate Experiment (GRACE) and satellite altimetry are suitable for the precise measurement of terrestrial water storage (TWS) and lake water level variations from space. In this study, two GRACE solutions, namely, spherical harmonics (SH) and mascon (MSC), are utilized with the Global Land Data Assimilation System (GLDAS) model to estimate the spatial and temporal variations of TWS in the Upper Indus Basin (UIB) for the study period of January 2003 to December 2016. The TWS estimated by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…Large-scale changes in TWS (right panel, Fig. 8) follow the pattern of bimodal precipitation distribution in the Indus Basin due to western disturbances and ISM (Hasson et al, 2016;Hussain et al, 2020). The northwest to southeast increase in storage (reduction of blue color intensity) during the winter months (December to February) and pre-monsoon months (March to May) can be attributed to western disturbances.…”
Section: Effect Of Filteringmentioning
confidence: 68%
“…Large-scale changes in TWS (right panel, Fig. 8) follow the pattern of bimodal precipitation distribution in the Indus Basin due to western disturbances and ISM (Hasson et al, 2016;Hussain et al, 2020). The northwest to southeast increase in storage (reduction of blue color intensity) during the winter months (December to February) and pre-monsoon months (March to May) can be attributed to western disturbances.…”
Section: Effect Of Filteringmentioning
confidence: 68%
“…The GRACE data have different output products, i.e., a spherical harmonic and mascon solution. The literature shows that mascon solutions have a higher correlation with the groundwater monitoring wells than the spherical harmonic dataset [28]. In this study, we have used the Centre for Space Research (CSR)-based monthly mascon solutions for TWS.…”
Section: Grace Tws Datasetmentioning
confidence: 99%
“…The GLDAS considers different hydrological components of LSMs. Various LSMs have been used by different researchers, but the Noah model from the GLDAS-based data is highly preferred by researchers [28]; therefore, the Noah model-based input parameters are used for GWS extraction in this study. The GLDAS input parameters units are converted from kg/m 2 to centimeters to make them consistent with the GRACE-based TWS data.…”
Section: Monthly Groundwater Storage Change (∆Gws)mentioning
confidence: 99%
“…Additionally, groundwater water storage components are missing in GLDAS model, which can be calculated from the GRACE signal. It has been observed that integrated total water content estimated by GRACE is comparable with the GLDAS model's TWS [1,23]. Therefore, these land surface state variables were derived, and then, the TWS from the GLDAS model is calculated.…”
Section: Gldas Modelmentioning
confidence: 99%
“…GRACE is a complement and can overcome the limitations of the other remotely sensed products and gauge station measurements with the main advantage that it provides water stored at all levels, including surface and sub-surface water, whereas the GLDAS-Noah model does not simulate the ground water storage [13]. However, according to the study conduct by [23], the ground water storage is stable (no apparent trend) in Upper Indus basin (UIB) as there is no any human intervention such as ground water pluming has been reported in the region. Therefore, ground water storage estimation has been neglected in this study.…”
Section: Introductionmentioning
confidence: 99%